Disruptive Innovation and Maritime Sector : Discovering smart-shipping’s potential to disrupt shipping - Martimo, Petri (fi=Turun yliopisto|en=University of Turku|, 2017)
Disruptive innovation has steadily increased its interest after Clayton Christensen introduced the concept of disruptive technologies in 1995. The concept of replacing learned values with new ones stems from competence theories, dynamic capabilities and resource-based view, thus it is appealing for business managers. The master’s thesis studies a disruptive innovation in the context of shipping, which is hypothesized as being in a verge of change even disruption. Fourth wave of smart-shipping is changing the shipping industry by making the ships more connected through developed ICT-systems following the concepts of internet of things and industry 4.0. thinking. In the 1990’s the internet revolutionized the world and many established firms struggled with new entrants with new set of skills and new business models. This thesis emphasizes the same kind of dilemma in which the established shipping firms could be struggling with resource allocation between traditional shipping and smart-shipping. Qualitative research was conducted by using interview as the method. Analysis was done by using theory guided content analysis methods which aims to develop a solid information integrity from the collected data. Total of seven marine companies and eight interviewees build the empirical data, all the companies having operations in the Baltic Sea area. Target companies were mostly small and middle-sized shipping companies who felt being innovative and rapid when encountering changes. In overall, all target companies were identified as opportunity- seekers with strong innovative organizational culture. Some of the smaller target companies were more willing to cannibalize their core business if the smart-shipping or even autonomous shipping would be disrupting their markets. The largest upcoming change was identified relating to integrations between different actors that are involved in the same shipping process. Before any larger change could develop, shipping would require more consolidation to have the balance between supply and demand. Smart-shipping was identified as a disruptive business model innovation. Disruption was discovered to start from the smart tugboat and ferry markets, encroaching upwards disrupting the feeder markets eventually replacing some of the existing short-sea and deep-sea container incumbents. Smart-shipping is highly digital related concept and further studies of digital disruption is needed. New digital innovations could be changing the the time or the investments required to develop disruptive innovations.